Shifts in Zooplankton Behavior Caused by a Mixture of Pesticides - Andrade, Victoria Soledad (2018)
Behavioral changes have been considered as appropriate to evaluate sublethal effects of pollutants. The aim of this study was to evaluate the effects of a mixture of pesticides, with glyphosate and 2,4-D (Gly + 2,4-D) as active ingredients, on the zooplankton evasion behavior from the fish Cnesterodon decemmaculatus. An increase in the evasion behavior was observed for copepods at two different concentrations of the Gly + 2,4-D mixture, for cladocerans at the lowest pesticide concentration, and for rotifers at the highest pesticide concentration. The response time to the fish signals also differed, being copepods faster than cladocerans and rotifers. All the exposed organisms showed higher variability in their distribution over time than those of controls (without pesticides). Our results suggest that the Gly + 2,4-D mixture formulations may have a mimetic effect with the fish alarm signals. The potential consequences of maladaptive responses triggered by pesticides, as well as the increased swimming activity, are discussed.